2011
DOI: 10.1002/gea.20349
|View full text |Cite
|
Sign up to set email alerts
|

Geoarchaeology of the Nehalem spit: Redistribution of beeswax galleon wreck debris by Cascadia earthquake and tsunami (∼A.D. 1700), Oregon, USA

Abstract: A coincidence of the Beeswax galleon shipwreck (ca. A.D. 1650-1700) and the last Cascadia earthquake tsunami and coastal subsidence at ϳA.D. 1700 redistributed and buried wreck artifacts on the Nehalem Bay spit, Oregon, USA. Ground-penetrating radar profiles (ϳ7 km total distance), sand auger probes, trenches, cutbank exposures (29 in number), and surface cobble counts (49 sites) were collected from the Nehalem spit (ϳ5 km 2 area). The field data demonstrate (1) the latest prehistoric integrity of the spit, (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The abrupt subsidence event (1.0-1.5 m of relative SLR in the study area) was widespread throughout the three subcells (Peterson et al, 2000). However, a corresponding catastrophic beach retreat scarp was only preserved at the northern end of the Tillamook subcell ( Figure 2), where ~150 m of interseismic beach width recovery occurred from interplate recoupling and regional tectonic uplift, after ~1750 (Peterson et al, 2010). No preserved catastrophic beach retreat scarps have been found by these authors from any other beaches in the three-subcells study area.…”
Section: Evidence Of Declining Beach Sand Reservesmentioning
confidence: 91%
See 3 more Smart Citations
“…The abrupt subsidence event (1.0-1.5 m of relative SLR in the study area) was widespread throughout the three subcells (Peterson et al, 2000). However, a corresponding catastrophic beach retreat scarp was only preserved at the northern end of the Tillamook subcell ( Figure 2), where ~150 m of interseismic beach width recovery occurred from interplate recoupling and regional tectonic uplift, after ~1750 (Peterson et al, 2010). No preserved catastrophic beach retreat scarps have been found by these authors from any other beaches in the three-subcells study area.…”
Section: Evidence Of Declining Beach Sand Reservesmentioning
confidence: 91%
“…Profile elevations were tied into predicted tide levels from mid-swash runups (±0.25 m error) measured during the time of predicted mean tide level (MTL±0.1 hour). Beach sand thickness was established at multiple backshore and mid-beach sites by 1) seismic refraction and trenching in the Cannon Beach subcell (Pettit, 1990; and 2) ground penetrating radar (GPR) and sand augering (Tillamook and Netarts subcells) (Doyle, 1996;Peterson et al, 2010). GPR was also used to test for coseismic beach retreat scarps in the Nehalem Bay, Tillamook Bay, and Netarts Bay sand spits (H. Jol and C. Peterson, unpublished data, 2001;Losey, 2003;Peterson et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The artifacts were tentatively traced to a lost Spanish galleon, possibly the San Francisco Xavier lost in 1705 (Giesecke, 2007) but the mechanism for the distribution of artifacts across the bay spit could not be explained. After geological studies established that tsunami cobbles and boulders were draped across the surface of the sand spit the across spit distribution of artifacts were attributed to nearfield tsunami surges (Peterson et al, 2011) resulting from the last Cascadia megathrust rupture (M w ~9.0) in 1700 (Satake et al, 1996). A renewed search of Spanish documents showed that another galleon Santo Cristo de Burgos had been lost in 1693, thereby permitting overland transport of artifacts by the 1700 Cascadia tsunami surges (Williams et al, 2017).…”
Section: Beeswax Galleon Shipwreckmentioning
confidence: 99%